2017
DOI: 10.1111/jgs.15157
|View full text |Cite
|
Sign up to set email alerts
|

Report and Research Agenda of the American Geriatrics Society and National Institute on Aging Bedside‐to‐Bench Conference on Urinary Incontinence in Older Adults: A Translational Research Agenda for a Complex Geriatric Syndrome

Abstract: The American Geriatrics Society, with support from the National Institute on Aging and other funders, held its ninth Bedside-to-Bench research conference, entitled "Urinary Incontinence in the Older Adult: A Translational Research Agenda for a Complex Geriatric Syndrome," October 16 to 18, 2016, in Bethesda, Maryland. As part of a conference series addressing three common geriatric syndromes-delirium, sleep and circadian rhythm disturbance, and urinary incontinence-the series highlighted relationships and pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 115 publications
(119 reference statements)
1
25
1
4
Order By: Relevance
“…Urinary incontinence (UI) is considered a geriatric syndrome, and is associated with multiple health‐related problems, including dermatitis, falls, lower activity of daily living (ADL), impairment of dignity and higher mortality . The prevalence of double incontinence (DI), both UI and fecal incontinence (FI), is high among individuals living in nursing homes, and the significant predictors for the development of DI are pre‐existing UI, greater functional or cognitive impairment, higher number of comorbidities, older age and lower quality of nursing home care .…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence (UI) is considered a geriatric syndrome, and is associated with multiple health‐related problems, including dermatitis, falls, lower activity of daily living (ADL), impairment of dignity and higher mortality . The prevalence of double incontinence (DI), both UI and fecal incontinence (FI), is high among individuals living in nursing homes, and the significant predictors for the development of DI are pre‐existing UI, greater functional or cognitive impairment, higher number of comorbidities, older age and lower quality of nursing home care .…”
Section: Introductionmentioning
confidence: 99%
“…Urinary symptoms increase in prevalence with aging, directly contributing to diminished quality of life, increased economic burden, and morbidity . Annual expenditures for urinary incontinence alone rivals that of all cancer care in the United States .…”
Section: Introductionmentioning
confidence: 99%
“…Annual expenditures for urinary incontinence alone rivals that of all cancer care in the United States . Despite an urgent need, available evaluative, and therapeutic strategies for urinary symptoms are often incomplete and inadequate, with palliative catheterization or containment remaining commonplace in older adults …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of people aged over 40 years reported an annual incontinence incidence rate of 6.3% . Some of the factors associated with UI in the older general population include age, frailty, falls, obesity, parity and comorbidities such as hypertension, diabetes, cognitive impairment, depression, urinary tract infection, stroke and mobility impairment …”
Section: Introductionmentioning
confidence: 99%